Structural network position and performance of health leaders within an HIV prevention trial - Mulawa, Marta I. (AIDS Behav, 2018)
The effectiveness of peer leaders in promoting health may depend on the position they occupy within their social networks. Using sociocentric (whole network) and behavioral data from the intervention arm of a cluster-randomized HIV prevention trial in Dar es Salaam, Tanzania, we used generalized linear models with standardized predictors to examine the association between heath leaders’ baseline structural network position (i.e., in-degree and betweenness centrality) and their 12-month self-reported 1) confidence in educating network members about HIV and gender-based violence (GBV) and 2) number of past-week conversations about HIV and GBV. As in-degree centrality increased, leaders reported fewer HIV-related conversations. As betweenness centrality increased, leaders reported greater number of conversations about GBV. Network position was not significantly associated with confidence in discussing either topic. Our results suggest that peer leaders who occupy spaces between subgroups of network members may be more effective in engaging their peers in sensitive or controversial topics like GBV than more popular peer leaders.